Rise of Islamic feminism in Shariah courts: Hauwa Ibrahim and shariah implementation in the Northern Nigeria - Zakariyah, Luqman (2015)
This paper discusses the rise and trends of Muslim/ Islamic feminism in the wake of application of Shariah in Northern Nigeria. It specifically studies the role of Hauwa Ibrahim in fighting for the rights of women in Shariah criminal cases and her approaches and strategies for winning the cases. It claims that though Hauwa Ibrahim's strategy does not overtly proclaim feministic approach, the feminist card had been played in the way she and her alliance had portrayed the cases. The claim of the feministic approach of Ibrahim is inferred from the analysis of criminal cases reported in Weimann article on Islamic Criminal Law in Northern Nigerian. The analysis elucidates and reveals that the number of female victims and the claim of women discrimination during the implementation of Shariah in Northern Nigeria are exaggerated.